Innate Signaling Networks in Mucosal IgA Class Switching - Chorny, Alejo (2010)
The past 20 years have seen a growing interest over the control of adaptive immune responses by the innate immune system. In particular, considerable attention has been paid to the mechanisms by which antigen-primed dendritic cells orchestrate the differentiation of T cells. Additional studies have elucidated the pathways followed by T cells to initiate immunoglobulin responses in B cells. In this review, we discuss recent advances on the mechanisms by which intestinal bacteria, epithelial cells, dendritic cells, and macrophages cross talk with intestinal T cells and B cells to induce frontline immunoglobulin A class switching and production.